Pengaruh Minat dan Lingkungan Belajar terhadap Prestasi Akademik Mahasiswa Institut Teknologi dan Bisnis Master - Mhd Suleman Hsb; Aswanto, Aswanto; Mukson, Mukson; Panzi Barza; Legia Seki Yolanda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the influence of learning interest and learning environment on the academic achievement of students in the Management Study Program at the Pekanbaru Master of Technology and Business Institute. The type of research used is quantitative research, which is research that focuses on data in the form of numbers and statistical analysis to answer research questions. The population in this study were 130 students in the 3rd and 5th semesters of management study programs, and the sample obtained in this study was 44 students. The data collection technique in this study used a closed questionnaire with a Likert scale of 1–5, where respondents were asked to provide answers according to the level of agreement with the statements given. This questionnaire was compiled based on variable indicators, namely learning interest, learning environment, and academic achievement. The data analysis technique carried out data processing using the SPSS 26 application. The results of this study indicate that learning interest and learning environment have a positive and significant influence on academic achievement. This means that the higher the learning interest and the better the learning environment, the student's academic achievement will also increase. Conversely, if the learning interest and environment are low, academic achievement tends to decrease.